(untitled) (Palimpsesto, 2018)
The film The Student suggests and discusses two antagonist hypotheses on politics and the return ofcollective subjects after the demise of neoliberalism and the unexpected rise of the Latin American Left.Before a purely instrumentalized form of power that is deprived of historicity, confined to the realm ofmaterial needs, and subsumed to the logics of patronage that structure the state-democratic order, standsanother one, more faithful to the event that gives it origin. Constituted as the only true one, this secondhypothesis on politics points no longer to domination, but to emancipation.